Non-Syndromic Tooth Agenesis in Two Chinese Families Associated with Novel Missense Mutations in the TNF Domain of EDA (Ectodysplasin A) - Li, Shufeng (Public Library of Science, 2008)
Here we report two unrelated Chinese families with congenital missing teeth inherited in an X-linked manner. We mapped the affected locus to chromosome Xp11-Xq21 in one family. In the defined region, both families were found to have novel missense mutations in the ectodysplasin-A (EDA) gene. The mutation of c.947A>G caused the D316G substitution of the EDA protein. The mutation of c.1013C>T found in the other family resulted in the Thr to Met mutation at position 338 of EDA. The EDA gene has been reported responsible for X-linked hypohidrotic ectodermal dysplasia (XLHED) in humans characterized by impaired development of hair, eccrine sweat glands, and teeth. In contrast, all the affected individuals in the two families that we studied here had normal hair and skin. Structural analysis suggests that these two novel mutants may account for the milder phenotype by affecting the stability of EDA trimers. Our results indicate that these novel missense mutations in EDA are associated with the isolated tooth agenesis and provide preliminary explanation for the abnormal clinical phenotype at a molecular structural level.